Analysis of the Influence of Budget Management, Management Information Systems, and Agile Leadership on Employee Engagement of the Trade and Industry Department of Sungai Penuh City - Asro Guswar Hakim; Afriyeni (SAFE-Network, 2026)
This study aims to analyze the influence of budget management, management information systems, and agile leadership on employee job satisfaction in the digital era at the Sungai Penuh City Trade and Industry Office. This study used a quantitative approach with a survey method, where data were analyzed using multiple linear regression to test partial and simultaneous effects between variables. The results showed that budget management had a positive and significant effect on employee job satisfaction, indicating that effective, transparent, and accountable budget management can support task implementation and increase comfort and security at work. Management information systems also proved to have a positive and significant effect, as the availability of accurate, timely, and easily accessible information helps improve work efficiency and reduce administrative burdens. Furthermore, agile leadership had a positive and significant effect on job satisfaction, indicating that an adaptive, communicative, and participatory leadership style can create a conducive work environment. Simultaneously, these three variables had a positive and significant effect on employee job satisfaction. The regression model used was able to explain most of the variation in job satisfaction, making these three factors important determinants in improving employee job satisfaction in the digital era.